Pengaruh Jarak Tanam dan Pemangkasan Tanaman pada Produksi dan Mutu Benih Koro Pedang (Canavalia enziformis) - Tatiek Kartika Suharsi; Memen Surahman; Silmy Fadilah Rahmatani (Institut Pertanian Bogor, 2013)
Jack bean potentially as a substitute of soybean. Increasing value of jack bean requirement of good quality of seeds. Availabelity of good quality seeds must be supported by teknology of production. Prunning and planting space are factors should be concidered. Field trial was carried out at Ciherang, Bogor. Using randomized block design, two kind of prunning and five level of planting space. Base on the research indicate that planting space did not influence to vegetatief growth and fisicaly also fisiologicaly seeds quality. Planting space influence to several parameter of yield.